2013
DOI: 10.1002/pros.22713
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the developing human fetal prostate in a rodent xenograft model

Abstract: Background Prostate cancer is the most commonly diagnosed non-skin cancer in men. The etiology of prostate cancer is unknown, although both animal and epidemiologic data suggest that early life exposures to various toxicants, may impact DNA methylation status during development, playing an important role. Methods We have developed a xenograft model to characterize the growth and differentiation of human fetal prostate implants (gestational age 12-24 weeks) that can provide new data on the potential role of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…The hormonal environment of the host is also a concern, as hormones play a vital role in prostatic growth. Our previous publication has demonstrated that the human xenografts display accelerated maturation, as shown by the expression of the adult smooth muscle marker caldesmon in 30-day xenografts 36 . It may also be necessary to use a castrated model that would allow controlling the hormones administered to our hosts as well as the xenograft exposure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The hormonal environment of the host is also a concern, as hormones play a vital role in prostatic growth. Our previous publication has demonstrated that the human xenografts display accelerated maturation, as shown by the expression of the adult smooth muscle marker caldesmon in 30-day xenografts 36 . It may also be necessary to use a castrated model that would allow controlling the hormones administered to our hosts as well as the xenograft exposure.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously described the procedure in detail in Saffarini et al 23 . Briefly, human prostate tissue was kept in ice-cold transport media (Leibovitz L-15, penicillin, streptomycin, and gentamycin) until surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have demonstrated vast reductions in primordial follicle reserve after transplantation and occasions of vascular thrombosis (Bedaiwy and Falcone, 2010;Bedaiwy et al, 2008;Imhof et al, 2006;Jeremias et al, 2002). The nude rat has been previously established as an appropriate xenotransplant model for studies of human tumour development (Dauchy et al, 2012) and prostate disease (Saffarini et al, 2013). Of greater interest is the report by Wolvekamp et al (2001), demonstrating the possibility of cryopreservation and subsequent transplantation of wombat ovarian tissue into nude rats.…”
Section: Primordial Primary Secondary Antralmentioning
confidence: 96%
“…The degree of host immunodeficiency required for the study may vary by tissue. For instance, athymic nude mice and Rowett nude (RNU) rats are T‐cell deficient, which is sufficient for some human fetal tissues, including testis (Heger et al., ; Spade et al., ) and prostate (Saffarini et al., ). More severely immunocompromised hosts such as SCID Beige mice may be optimal for other tissues, as is the case for transplantation of human fetal lung (De Paepe et al., ).…”
Section: Considerations For Development Of Xenotransplantation Modelsmentioning
confidence: 99%
“…In this review, we describe our recent development of xenotransplant models with the goal of studying the effects of xenobiotics in human fetal testis (Heger et al., ; Spade et al., ), prostate (Saffarini et al., ), lung (De Paepe et al., , ), liver, and adipose tissue (Garcia et al., ). We do not aim to conduct an exhaustive review of the extensive literature on xenotransplantation.…”
Section: Introductionmentioning
confidence: 99%